Melatonin Rhythm and Its Relation to Sleep and Circadian Parameters in Children and Adolescents With Autism Spectrum Disorder - Martinez-Cayuelas, Elena; Gavela-Pérez, Teresa; Rodrigo-Moreno, María; Merino-Andreu, Milagros; Vales-Villamarín, Claudia; Pérez-Nadador, Iris; Garcés, Carmen; Soriano-Guillén, Leandro (Frontiers in Neurology, 2022)
Introduction Sleep problems are prevalent among individuals with autism spectrum disorder (ASD), and a role has been attributed to melatonin in this multifactorial comorbidity. Methods A cross-sectional study was conducted on 41 autistic children and adolescents (9.9 ± 3.02) and 24 children and adolescents with a normal intellectual function (8.42 ± 2.43) were used as controls. Subjects were matched for sex, body mass index, and pubertal stage, and all were drug-naive. Circadian and sleep parameters were studied using an ambulatory circadian monitoring (ACM) device, and saliva samples were collected around the onset of sleep to determine dim light melatonin onset (DLMO). Results Prepubertal individuals with ASD presented later DLMO and an earlier decline in melatonin during adolescence. A relationship was found between melatonin and both sleep and circadian parameters. Participants and controls with later DLMOs were more likely to have delayed sleep onset times. In the ASD group, subjects with the later daytime midpoint of temperature had a later DLMO. Later melatonin peak time and DLMO time were related to lower general motor activity and lower stability of its rhythms. Conclusion The melatonin secretion pattern was different in individuals with ASD, and it showed a relationship with sleep and circadian parameters. Alterations in DLMO have not been previously reported in ASD with the exception of more variable DLMO timing; however, high variability in the study design and sample characteristics prevents direct comparison. The ACM device enabled the measurement of circadian rhythm, a scarcely described parameter in autistic children. When studied in combination with other measures such as melatonin, ACM can offer further knowledge on sleep problems in ASD.